Older adults and games from a perspective of playability, game experience and pervasive environments: A systematics literature review - Cardona, Johnny Salazar (2022)
Games have had a growth and have been applied in different areas other than fun or entertainment. In the case of older adults, they are used as a mechanism to increase physical activity or improve cognitive training. Traditionally, games generate entertainment through consoles with motion sensors, traditional digital games or mobile devices. These initiatives can be improved when used in older adults considering the particularities of these people. Improvements can focus on both the gameplay and the design of the experience offered to the player as well as their subsequent evaluation. For this reason, we conducted a systematic review of the literature to identify the actual advances in these areas. Also, through the review it was possible to identify that games have been used to generate deeper and more complete experiences such as those offered by pervasivity in a variety of contexts.